Differential proteomic profile of spermatogenic and Sertoli cells from peri-pubertal testes of three different bovine breeds - Tripathi, Utkarsh K.; Aslam, Muhammad K. M.; Pandey, Shashank; Nayak, Samiksha; Chhillar, Shivani; Srinivasan, A.; Mohanty, T. K.; Kadam, Prashant H.; Chauhan, M. S.; Yadav, Savita; Kumaresan, Arumugam (Frontiers in Cell and Developmental Biology, 2014)
Sub-fertility is one of the most common problems observed in crossbred males, but the aetiology remains unknown in most of the cases. Although proteomic differences in the spermatozoa and seminal plasma between breeds have been investigated, the possible differences at the sperm precursor cells and supporting/nourishing cells have not been studied. The present study reports the differential proteomic profile of spermatogenic and Sertoli cells in crossbred and purebred bulls. Testis was removed by unilateral castration of 12 peri-pubertal bulls (10 months age), four each from crossbred (Holstein Friesian X Tharparkar), exotic purebred (Holstein Friesian) and indigenous purebred (Tharparkar) bulls. Spermatogenic and Sertoli cells were isolated and subjected to proteomic analysis. Protein extracts from the Sertoli and spermatogenic cells of each breed were analysed with 2-dimensional difference gel electrophoresis (2D-DIGE) and analysed with DecyderTM software. Compared to Holstein Friesian, 26 protein spots were over expressed and 14 protein spots were under expressed in spermatogenic cells of crossbred bulls. Similarly, 7 protein spots were over expressed and 15 protein spots were under expressed in the spermatogenic cells of Tharparkar bulls compared to that of crossbred bulls. Out of 12 selected protein spots identified through mass spectrometry, Phosphatidyl ethanolamine binding protein was found to be over expressed in the spermatogenic cells of crossbred bulls compared to Tharparkar bulls. The protein, gamma actin was found to be over expressed in the Sertoli cells of Holstein Friesian bulls, whereas Speedy Protein-A was found to be over expressed in Sertoli cells of crossbred bulls. It may be concluded that certain proteomic level differences exist in sperm precursor cells and nourishing cells between breeds, which might be associated with differences in the fertility among these breeds.